Dihydrocapsaicin Inhibits Cell Proliferation and Metastasis in Melanoma via Down-regulating β-Catenin Pathway - Shi, Shaomin; Li, Chongyang; Zhang, Yanli; Deng, Chaowei; Liu, Wei; Du, Juan; Li, Qian; Ji, Yacong; Guo, Leiyang; Liu, Lichao; Hu, Huanrong; Liu, Yaling; et al. (Frontiers in Oncology, 2021)
Dihydrocapsaicin (DHC) is one of the main components of capsaicinoids in Capsicum. It has been reported that DHC exerts anti-cancer effects on diverse malignant tumors, such as colorectal cancer, breast cancer, and glioma. However, studies focused on the effect of DHC upon melanoma have rarely been done. In the present study, melanoma A375 and MV3 cell lines were treated with DHC and the cell proliferation, migration, and invasion were significantly suppressed. Furthermore, DHC effectively inhibited xenograft tumor growth and pulmonary metastasis of melanoma cells in NOD/SCID mice model. It was identified that β-catenin, which plays significant roles in cell proliferation and epithelial-mesenchymal transition, was down-regulated after DHC treatment. In addition, cyclin D1, c-Myc, MMP2, and MMP7, which are critical in diverse cellular process regulation as downstream proteins of β-catenin, were all decreased. Mechanistically, DHC accelerates ubiquitination of β-catenin and up-regulates the beta-transducin repeat containing E3 ubiquitin protein ligase (BTRC) in melanoma cells. The DHC induced suppression of cell proliferation, migration, and invasion were partly rescued by exogenous β-catenin overexpression, both in vitro and in vivo. Taken together, DHC may serve as a candidate natural compound for human melanoma treatment through β-catenin pathway.